A Path Toward Inclusive Social Cohesion: The Role of European and National Identity on Contesting vs. Accepting European Migration Policies in Portugal - Pinto, Isabel R.; Carvalho, Catarina L.; Dias, Carina; Lopes, Paula; Alves, Sara; de Carvalho, Cátia; Marques, José M. (Frontiers in Psychology, 2020)
The Western hemisphere has witnessed recent immigration flows that hit European Union (EU), one leading destination for immigration. This immigration flows generated social and political debate across Europe. In one view migration flows represent an opportunity to construct a diverse social cohesion based on the respect for ethnic groups. Portuguese Government supports this view, being in line with the European Commission’s position. In another view, migration flows are perceived as a threat to existent national cultures. This view is held by political nationalisms and right-wing populism forces installed in the majority of EU countries’ parliaments, leading to the support of exclusive policies and citizens’ contestation of immigrants’ entrance. Nevertheless, this view accentuates untrusting social interactions sustained in discrimination against immigrants that already live in Europe, and thus, to unhealthy social cohesion. We theorize that European identity predicts positive attitudes towards immigrants (prosocial behavior and support for inclusive policies), whereas National identity’s predictions of attitudes towards immigrants’ inclusion depends on participants’ political tendency. Moreover, we test the mediation effect of positive (humanitarian concerns and economic benefit) and negative (jobs scarcity, cultural deterioration and invasion) arguments used in political discourses regarding immigrants’ inclusion on the relation between National and European identities and attitudes towards immigrants’ inclusion. Results (Portuguese sample, N = 176) show that national identity predicts negative attitudes towards immigrants’ inclusion, but only among right-wing individuals. This group is more susceptible to arguments focused on immigrants’ invasion and cultural deterioration, arguments that imply discrimination (devaluation) of immigrants. Contrarily, among those with left-wing political orientation, national identity predicts less contestation to immigrant’s inclusion sustained by humanitarian concerns. Interestingly, European identification weakened right-wing individuals’ adherence to discriminatory arguments and, simultaneously, increased the perceived positive economic contribution that immigrants bring to the host society, thus, increasing agreement with immigrants’ inclusion and prosocial behavior regarding them. We discuss these results by suggesting that the strength of European Identity sustained in humanitarian values among EU citizens may stimulate the construction of multicultural social cohesion, intergroup trust and social wellbeing based on democratic values, social justice and equality, and on the respect for human dignity.